Genomic imprinting: history and embryology - Solter, Davor (Henry Stewart Talks, 2007)
Emergence of imprinting as a concept from experiments involving reciprocal nuclear transfer in the mouse zygote, construction of embryos containing only the male genome (androgenones) or the female genome (gynogenones), functional differences between male and female genomes necessitating that both be present to ensure normal development and establishing that these differences occur during gametogenesis by imprinting, identification and characterization of imprinted genes, initial experiments leading to the conceptualization of imprinting and its developmental consequences
Reviewed at 2022/04/12